An ABC-VEN Analysis for Outpatient Medicines Use in the Department of Internal Medicine at Universitas Airlangga Teaching Hospital - Zedny Norachuriya; Budi Suprapti; Dinda Monika Nusantara Ratri; Cahyo Wibisono Nugroho; Yosiyanita Safari (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2024)
Background: Application of the ABC-VEN method in evaluating drug planning can increase efficiency and ensure optimal medicine availability and stable access to medications. Objective: To analyze ABC-VEN combinations to examine the profile of medicine use in the internal medicine department. Methods: This was an observational study with retrospective prescription data from outpatients in the Internal Medicine Department from January to March 2020. Collected data included the type, number of medicines, and medicine prices. Patients undergoing chemotherapy and retroviral therapy for HIV were excluded from the study. Subsequently, an ABC-VEN analysis was performed. Results: Of 4,242 prescription samples, 188 types of medicines were used. Based on the drug use evaluation with ABC analysis, category A contained 23 items (12.17%), category B contained 35 items (18.52%), and category C contained 130 items (69.31%). The ABC analysis for investment value found that category A contained eight items (4.23%), category B contained 22 items (11.64%), and 158 items (84.13%). Based on the VEN analysis, Group V had six medicine items, Group E had 152 medicine items, and Group N had 30 medicine items. The ABC-VEN investigation showed that there were eight, 151, and 29 items of medicines in Categories I, I, and III, respectively. Conclusion: Although there are medicines that are highly used, their investment value is quite low. The use of the ABC-VEN method to evaluate medicine use is crucial for organizing and controlling the medicine supply.